Atrakcyjność projektu metodologii praktycznej i epistemologii cnoty dla badań historyczno-gospodarczych - Bębnowski, Damian (Annales. Etyka w Życiu Gospodarczym, 2015)
Ewa Domańska, Professor at the Adam Mickiewicz University in Poznań (Poland)and Stanford University (USA), historian of historiography and methodologist ofhistory, formulated interesting comments about the state of humanities and socialsciences. The development of interdisciplinary research causes the interpenetrationof different disciplines. Although this kind of research is promising, inspiring aswell as influencing the development of science, careless research may cause somethreats in the longer term. According to Domańska, the lack of qualifications andreliability in this area (especially in the area of theory and methodology) underminesthe authonomy of the main disciplines and decline in the professionalism of research.This led the author to create the project, which aims to defend the independenceof the threatened disciplines as well as their ‘re-professionalisation’. It can beachieved by strongly emphasizing the role of theory in science; a strong embeddementof a discipline in the theory. Domańska’s concept can be a recipe, which isa dichotomic project. Firstly, it supposes a ‘practical methodology’, which is a constructingof the theory thanks to empirical research material. Secondly, it supposesa ‘virtue epistemology’, which is the ethical aspect of the researcher’s attitude andhis work.The aim of the paper is to discuss Domańska’s project and underline the originalityof her concept in the context of economic and social sciences. The economichistory is a specific discipline which develops at the crossroad of history and economics.It lets me put forward the thesis that Domańska’s suggestions are relevantto the research of economic history. I will show what cognitive chances are theresult of the ontology of economic history. I will question what the possible threatsare for the main disciplines (history and economics) as a result of the lack of professionalismin the interdisciplinary research of the economic past, and ask if Domańska’sproject is attractive for the economic history research thanks to the strongsetting in the ‘practical methodology’ in the theory. I also ask what the role of newtheoretical approaches in that area is, and whether it is possible to formulate innovatoryconceptions in the economic history. Finally, I question the role of ‘virtueepistemology’ or the ethical aspect of an economic historian’s work.